2019
DOI: 10.1038/s41398-018-0336-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between midlife serum high-density lipoprotein and mild cognitive impairment and dementia after 19 years of follow-up

Abstract: A third of dementia cases could be attributable to modifiable risk-factors. Midlife high-density lipoprotein cholesterol (HDL-C) is a measure which could help identify individuals at reduced risk of developing age-related cognitive decline. The Japan Public Health Centre-based prospective (JPHC) Study is a large population-based cohort which started in 1990. This study included 1299 participants from Saku area in Nagano prefecture. Participants had HDL-C measured in 1995–1996, and underwent a mental health scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 46 publications
8
58
4
Order By: Relevance
“…No signi cant differences were found for other lipids and lipoproteins. These results agreed with those obtained by other authors [28,29], who found that cognitive dysfunction is associated with a progressive decline in plasma HDL-cholesterol concentrations This underscores the protective effects of increased plasma HDL-cholesterol and its role in maintaining superior cognition in longevity [30]. Biomarkers, cognitive status, and physical strength…”
Section: Biomarkers and Cognitive Statussupporting
confidence: 92%
“…No signi cant differences were found for other lipids and lipoproteins. These results agreed with those obtained by other authors [28,29], who found that cognitive dysfunction is associated with a progressive decline in plasma HDL-cholesterol concentrations This underscores the protective effects of increased plasma HDL-cholesterol and its role in maintaining superior cognition in longevity [30]. Biomarkers, cognitive status, and physical strength…”
Section: Biomarkers and Cognitive Statussupporting
confidence: 92%
“…In particular, women showed a considerable increase in dementia after 60 years. In the same context, a recent study on the Japanese population showed that high midlife HDL-C levels are inversely associated with both late-life MCI and dementia [31]. Other studies with the American population also showed that higher HDL cholesterol levels are associated with better cognitive function [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similar processes may drive the association detected here. With regard to lipd metabolism, it was showed previously that high levels of total cholesterol and low-density lipoprotein (LDL) cholesterol, were associated with cognitive decline in older population [44], and that low-level of high-density lipoprotein (HDL) cholesterol is a risk factor for deficit and decline in memory in midlife [67, 68]. HDL cholesterol is critical for the maturation of synapses and maintenance of synaptic plasticity while LDL cholesterol is a proven risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%